Occupational health regulation the case of women workers in selected economic zones in the Philippines - Lu, Jinky Leilani (2003)
This study investigates the impact of information technology and gender relations in two manufacturing industries, namely, garments and electronics, in the Philippines on the health and nature of work of women workers. It consists of a cross-sectional study of 23 establishments, 630 respondents, and 47 supervisors. Methodology consists of questionnaires, walk-through survey of industries and interviews. The study shows that the overall physical health of supervisors is affected by factors such as number of workers supervised: burdensome, fast-paced, and toxic nature of work; overtime; and lack of job autonomy. Workers' health is also affected by close monitoring, poor quality of work and hazard exposures. Results show that gender segregation is evident in companies, that new management styles and production processes adversely affect the health of women, and that information technology has brought about several organizational changes affecting women's nature of work. The data were analyzed in the light of existing regulations of the four books of the Labor Code of the Philippines. Policy and advocacy work implications are recommended based on the results of the study.
Keywords: Women employees -- Social conditions; Economic processing zones; Electronics industries; Garment industry; Health and safety standards; Occupational health regulation; Government regulation